2014
DOI: 10.1016/j.ijosm.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic reasoning in osteopathy – A qualitative study

Abstract: Background: The clinical reasoning processes which result in the forma-tion of a diagnosis, are fundamental for safe, effective and efficient clinical prac-tice and are central to professional autonomy and accountability. While research has identified the diagnostic reasoning approaches taken by a range of healthcare professions, there is limited understanding of how osteopaths formulate diagnoses in clinical practice. Objectives: The aim of this research was to explore the diagnostic reasoning of experienced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 50 publications
4
20
0
Order By: Relevance
“…8 The process of refining, accepting and discarding hypotheses evident in this study is consistent with hypothetico-deductive reasoning approaches described in a wide range of other health professions including: medicine, 32,50 physiotherapy 2,51 and osteopathy. 27,36 The application of both pattern recognition and hypothetico-deductive reasoning together is consistent with diagnostic reasoning literature in medicine 32,34,52 and physiotherapy. 2,53,54 As a component of diagnostic reasoning, palpation was utilised by the participating osteopaths, especially during periods of uncertainty to complement physical assessment procedures (such as orthopaedic and special testing).…”
Section: Main Findingssupporting
confidence: 71%
See 4 more Smart Citations
“…8 The process of refining, accepting and discarding hypotheses evident in this study is consistent with hypothetico-deductive reasoning approaches described in a wide range of other health professions including: medicine, 32,50 physiotherapy 2,51 and osteopathy. 27,36 The application of both pattern recognition and hypothetico-deductive reasoning together is consistent with diagnostic reasoning literature in medicine 32,34,52 and physiotherapy. 2,53,54 As a component of diagnostic reasoning, palpation was utilised by the participating osteopaths, especially during periods of uncertainty to complement physical assessment procedures (such as orthopaedic and special testing).…”
Section: Main Findingssupporting
confidence: 71%
“…An "interplay" of both of these strategies was observed, where the perceived degree of complexity and familiarity determined which strategy would be used. 27 In the context of the current study, findings from the consultation maps identified that all participating osteopaths predominantly utilised hypothetico-deductive reasoning and pattern recognition, transitioning dynamically between both strategies during the observed clinical encounters. This transitioning is consistent with the work of Thomson et al 27 and, to our knowledge, is the second study to illustrate the dynamic use of both diagnostic reasoning strategies in an osteopathic consultation.…”
Section: Main Findingsmentioning
confidence: 74%
See 3 more Smart Citations